Polycaprolactone-based scaffold for oil-selective sorption and improvement of bacteria activity for bioremediation of polluted water: Porous PCL system obtained by leaching melt mixed PCL/PEG/NaCl composites: Oil uptake performance and bioremediation efficiency. (June 2017) - Scaffaro, Roberto; Lopresti, Francesco; Catania, Valentina; Santisi, Santina; Cappello, Simone; Botta, Luigi; Quatrini, Paola
Graphical abstract: Highlights: Biopolymeric sponge (ORS) for selective sorption of different oily waste from water. ORS has a 500 wt% of oil uptake and high reusability up to 50 cycles. The ORS compressive modulus was found to be very close to that of virgin one up to 25 cycles. ORS compressive modulus after 25 cycles was found to be similar to that of virgin one. Abstract: A novel floatable and biodegradable sponge for the selective absorption of oil from water and potentially useful as cell carrier for bioremediation treatments was prepared in polycaprolactone (PCL). The eco-friendly process for fabricating the PCL sponge does not involve either synthetic routes or organic solvents, thus minimizing environmental hazard. In particular, the 3D porous materials have been prepared by mixing in the melt the polymer matrix with two water-soluble porogen agents (NaCl and PEG) and thereafter leaching the obtained PCL/NaCl/PEG composites in water. The PCL sponges here proposed are capable to remove different types of oily pollutants (up to 500 wt%), and were successfully tested as carrier materials of hydrocarbon(HC)-degrading bacteria for bioremediation. The bioremediation efficiency of the scaffold-bacteria system was analyzed on crude oil and n -alkanes using two highly performant HC-degrading bacterial strains: the marine hydrocarbonoclastic model strain Alcanivorax borkumensis SK2 and the soil long-chain n -alkane degrader Nocardia sp. SoB. Morphological analysis highlighted a high capacity of adhesion and proliferation of bacterial cells within the whole interconnected three-dimensional structure. HC degradation rates, evaluated by GC-FID analysis, demonstrated the higher degrading performance of immobilized-cells if compared with conventional submerged liquid culture.